2022
DOI: 10.1126/scitranslmed.abn3715
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 S2–targeted vaccination elicits broadly neutralizing antibodies

Abstract: Several variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have emerged during the current coronavirus disease 2019 (COVID-19) pandemic. Although antibody cross-reactivity with the spike glycoproteins (S) of diverse coronaviruses, including endemic common cold coronaviruses (HCoVs), has been documented, it remains unclear whether such antibody responses, typically targeting the conserved S2 subunit, contribute to protection when induced by infection or through vaccination. Using a mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 99 publications
6
73
0
Order By: Relevance
“…This was not exactly the case in our study, indicating that in addition to imprinted memory, responses targeting novel antigens can be generated. Besides the RBD, antibodies targeting other regions of the spike, such as the NTD or S2 region may also broaden the humoral response 60,61 . The interval between prior SARS-CoV-2 infection and booster vaccination impacts magnitude and quality of antibody and B cell responses 62 .…”
Section: Discussionmentioning
confidence: 99%
“…This was not exactly the case in our study, indicating that in addition to imprinted memory, responses targeting novel antigens can be generated. Besides the RBD, antibodies targeting other regions of the spike, such as the NTD or S2 region may also broaden the humoral response 60,61 . The interval between prior SARS-CoV-2 infection and booster vaccination impacts magnitude and quality of antibody and B cell responses 62 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no report so far about the clinical or per-clinical studies on SARS-CoV-2 vaccines targeting the S2 subunit, although Ng et al has reported that a DNA vaccine containing genes encoding membrane-bound SARS-CoV-2 S2 subunit can induce bnAbs against sarbecoviruses, while the bacterially produced recombinant S2 protein cannot elicit bnAbs. 85 These results, together with those from our study, suggest that these S2-specific bnAbs isolated from the SARS-CoV-2-infected or vaccinated individuals may be elicited by the neutralizing epitopes in the conserved regions of S2 subunit at a special fusion conformation (e.g., prefusion, fusion intermediate or post-fusion conformation), while our HR121 vaccine can induce potent bnAb responses in the vaccinated animals, possibly because HR121 vaccine contains the transiently exposed neutralizing epitopes in the HR1 region of S2 subunit present in the fusion intermediate conformation. Therefore, it is both a great opportunity and a challenge to design an effective S2 subunit vaccine containing the exposed neutralizing epitopes in the conserved regions of S2 subunit at a proper conformation that can induce potent and broad-spectrum cross-nAb responses.…”
Section: Discussionmentioning
confidence: 99%
“…In a paper published in Science Translational Medicine in July the team reported that mice had created antibodies able to neutralise other animal and human coronaviruses, including the seasonal "common cold," the alpha, beta, and delta variants, the original omicron variants, and two bat coronaviruses. 10 And DIOSynVax, a biotech spinout from the University of Cambridge, is developing an mRNA vaccine that could protect against a number of coronaviruses including SARS-CoV-1, SARS-CoV-2, and MERS. In March it received a $42m (£38m; €43m) award from the Coalition for Epidemic Preparedness Innovations.…”
Section: What About Pan-coronavirus Vaccines?mentioning
confidence: 99%
“…Another team, based at the Francis Crick Institute in the UK, is in the early stages of testing a candidate targeting a specific area of the spike protein known as the S2 subunit, which allows the virus to fuse with the host cell. In a paper published in Science Translational Medicine in July the team reported that mice had created antibodies able to neutralise other animal and human coronaviruses, including the seasonal “common cold,” the alpha, beta, and delta variants, the original omicron variants, and two bat coronaviruses 10…”
Section: What About Pan-coronavirus Vaccines?mentioning
confidence: 99%